Ovarian histomorphological changes in rats supplemented with edible bird's nest - Albishtue, Abdulla A.; Degu, Nurhusien Yimer; Zakaria, M. A.; Haron, Abd Wahid; Yusoff, Rosnina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Edible Bird’s Nest (EBN) is an animal product from the saliva secretion of male swiftlet birds (Aerodramus fuciphagus and Aerodramus maximus). It is traditionally consumed among Asians for its nutritional and medicinal values. The objective of this study was to evaluate the effect of EBN supplement on the ovarian activities of female rats through histomorphometric analysis. A total of 24 Sprague dawley rats, divided into 4 equal groups (G): G1 as untreated control group, G2, G3 and G4 as treated groups with EBN at graded concentrations of 30, 60 and 120 mg/kg of body weight per day for 8 weeks, respectively were used. During the treatment period, body weight of each rats were recorded weekly. After sacrificing the rats under general anaesthesia at proestrus, the ovaries excised and weighed and measured in length. The samples at the level of the ovary of similar site fixed in 10% formalin for 24 hrs, sectioned and stained using Haematoxylin and Eosin (H&E) stain and observed under a microscope for histological changes. Results showed increased length and weight of ovary in G4 (P<.05) compared to other groups. A parallel increase in the number of all types of surviving follicles across treatment groups with increase in the dose of EBN supplemented were recorded. Similarly, thickness of the ovarian surface epithelium as well as the number of interstitial cells in G4, were higher (P< 0.05) than the other groups. In conclusion the study revealed that EBN supplement enhances proliferation of ovarian follicular structures and ovarian-body weight ratio in rats.